PEMBENTUKAN SATUAN PERLINDUNGAN MASYARAKAT (SATLINMAS) DI KECAMATAN SAMBAS KABUPATEN SAMBAS - Ramli (Cross-border, 2025)
Regulation of the Minister of Home Affairs Number 26 of 2020 concerning the Organization of Public Order and Community Tranquility and Community Protection mandates village heads to form Satlinmas at the village level. The existence of Satlinmas is essential for maintaining security and order in the village. However, in the Sambas District of Sambas Regency, there are still villages that have not formed Satlinmas. In addition, there are Satlinmas units whose membership does not comply with regulations. The focus of this research is on how Satlinmas is formed in the Sambas District, as well as the factors that hinder the implementation of the Regulation of the Minister of Home Affairs Number 26 of 2020 concerning the Organization of Public Order and Community Tranquility and Community Protection in the Formation of Satlinmas in the Sambas District. This type of research is qualitative, characterized by field research with an empirical approach that examines phenomena occurring in the field related to the behavior of communities or institutions based on observation and facts, so the results are not speculative. To obtain data, observations, interviews, and documentation were conducted. The conclusion of this study is that the Regulation of the Minister of Home Affairs Number 26 of 2020 concerning the Organization of Public Order and Community Peace as well as Community Protection in the Formation of Satlinmas in Sambas District has not been fully implemented. This is evident from several indicators, namely: the formation and structure of Satlinmas, the implementation of duties and functions, and the recruitment process of Satlinmas members. The factors causing the incomplete implementation include: Satlinmas membership, limited funding, the relatively advanced age of Satlinmas members, motivation and interest in becoming Satlinmas members, and the lack of training for Satlinmas members.